Determination of particulate organic carbon sources to the surface mixed layer of the Canada Basin, Arctic Ocean. Issue 2 (15th February 2014) - Brown, Kristina A.; McLaughlin, Fiona; Tortell, Philippe D.; Varela, Diana E.; Yamamoto‐Kawai, Michiyo; Hunt, Brian; Francois, Roger
Abstract Stable isotope ratios of particulate organic carbon (POC), together with other tracers, were analyzed in samples from the Canada Basin surface mixed layer in 2008 and 2009. Sampling was conducted during the end of the 2008 melt season and at the beginning of the 2009 freezeup under a variety of surface conditions, including open water, newly formed seasonal ice, and multiyear ice. In both years, POC exhibited a wide isotopic range (δ13C‐POC −24.5 to −31.1‰), with the most isotopically depleted material generally found in the central basin. Isotopically enriched material was found on the shelves, consistent with higher biological production and strongly correlated with in situ carbon‐uptake rates. In contrast, offshore in the central basin, there was no significant relationship between δ13C‐POC distributions and either chlorophyll a or aqueous CO2 concentrations, suggesting that in situ biological production was not the dominant control. Analysis of freshwater sources suggested that the sea ice melt contribution of POC to surface waters in the central Canada Basin exerted a negligible influence on δ13C‐POC distributions, and instead isotopically depleted POC in the surface waters of the central Canada Basin were sourced externally through advective transport of riverine organic matter. We show that alkalinity and meteoric water content can be used to distinguish POC inputs from North American and Russian rivers and our analysis suggests that Russian river inputs are the predominant source of 13C‐depleted organic matter to the mixed layer of the central Canada Basin.